2015
DOI: 10.5194/se-6-1237-2015
|View full text |Cite
|
Sign up to set email alerts
|

Predicting parameters of degradation succession processes of Tibetan <i>Kobresia</i> grasslands

Abstract: Abstract. In the past two decades, increasing human activity (i.e., overgrazing) in the Tibetan Plateau has strongly influenced plant succession processes, resulting in the degradation of alpine grasslands. Therefore, it is necessary to diagnose the degree of degradation to enable implementation of appropriate management for sustainable exploitation and protection of alpine grasslands. Here, we investigated environmental factors and plant functional group (PFG) quantity factors during the alpine grassland succ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 36 publications
3
32
0
3
Order By: Relevance
“…This finding is in agreement with a previous study in fenced alpine meadow (Wu et al, 2009). It is also consistent with the result of Lin et al (2015), which showed that plant functional group shifted from rhizome bunch grasses to rhizome plexus and dense plexus grasses during the degradation process in alpine meadow. It is worthwhile emphasizing that the importance of establishing and maintaining grassland communities with high diversity of dominant species and functional groups for grassland restoration has been previously recognized (Bai et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with a previous study in fenced alpine meadow (Wu et al, 2009). It is also consistent with the result of Lin et al (2015), which showed that plant functional group shifted from rhizome bunch grasses to rhizome plexus and dense plexus grasses during the degradation process in alpine meadow. It is worthwhile emphasizing that the importance of establishing and maintaining grassland communities with high diversity of dominant species and functional groups for grassland restoration has been previously recognized (Bai et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Generally, grassland desertification is considered as the loss of the ability of a landscape to provide ecosystem services due to a change in soil properties, vegetation, or climate (D'Odorico et al 2013). The process of grassland degradation and desertification is complex in view of the diversity of factors influencing grassland degradation and desertification, including natural factors (e.g., climate, fire, and species invasion) and anthropogenic factors (e.g., overgrazing and reclamation; Gong et al 2015, Lin et al 2015, Hu et al 2016, Pereira et al 2016. It could involve a decrease of greenness and productivity, along with biodiversity loss; but it also could relate to an increase of greenness due to shrub encroachment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that there may be a secondary successional change from swamp to swamp meadow and mature meadow and that soil water availability may be the main driver of this successional process (Ma et al, 2014;He and Richards, 2015;Lin et al, 2015). At the same time, plant functional traits play an important role in predicting the patterns of species composition, community structure, and their responses to environment change, which has drawn substantial ecological interest (e.g., Wright et al, 2004;McGill et al, 2006;Pérez et al, 2014;Li et al, 2015a); however, it is not clear whether functional traits and functional diversity (i.e., the identity, abundance, and range of species in a given community) can reflect the changes in soil properties during wetland drying on the Tibetan Plateau.…”
mentioning
confidence: 99%